2010
DOI: 10.1080/02626661003747556
|View full text |Cite
|
Sign up to set email alerts
|

Inferring groundwater system dynamics from hydrological time-series data

Abstract: The problem of identifying and reproducing the hydrological behaviour of groundwater systems can often be set in terms of ordinary differential equations relating the inputs and outputs of their physical components under simplifying assumptions. Conceptual linear and nonlinear models described as ordinary differential equations are widely used in hydrology and can be found in several studies. Groundwater systems can be described conceptually as an interlinked reservoir model structured as a series of nonlinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 38 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The two techniques applied are: multiple linear regression (STEPWISE) and evolutionary polynomial regression (EPR). These techniques have been used for modelling the water related applications (Mountains 2013;Doglioni et al 2010) and achieved good results.…”
Section: Modelled Daily Per Capita Usage With Household Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two techniques applied are: multiple linear regression (STEPWISE) and evolutionary polynomial regression (EPR). These techniques have been used for modelling the water related applications (Mountains 2013;Doglioni et al 2010) and achieved good results.…”
Section: Modelled Daily Per Capita Usage With Household Characteristicsmentioning
confidence: 99%
“…This technique has been used in a number of other applications, such as evapotranspiration process (El-Baroudy et al 2010), rainfall-groundwater dynamics (Doglioni et al 2010), water distribution and wastewater networks (Berardi et al 2008), and have shown good performance.…”
Section: Models Based On Evolutionary Polynomial Regression (Epr)mentioning
confidence: 99%
“…This method was adopted because it can derive simple and interpretable mathematical equations for parameter estimation and data prediction (Giustolisi & Savic, 2006). It has also been proven effective in modelling environmental and hydrological phenomena, particularly those involving high nonlinearity and uninterpretable dynamics (Doglioni, Mancarella, Simeone, & Giustolisi, 2010;Vassallo, Doglioni, Grimaldi, Di Maio, & Simeone, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…conflicting objectives; Giustolisi & Savic 2009). The EPR has already been applied successfully to other complex civil engineering problems, see for example Javadi & Rezania (2009), Berardi et al (2008, Doglioni et al (2010) and Laucelli & Giustolisi (2on).…”
Section: Introductionmentioning
confidence: 98%